Correlation of Renal Tissue Oxygenation to Venous, Arterial, and Capillary Blood Gas Oxygen Saturation in Preterm Neonates - Harer, Matthew W.; Gadek, Lauren; Rothwell, Amy C.; Richard, Luke; Starr, Michelle C.; Adegboro, Claudette O. (American Journal of Perinatology, 2023)
Objective The aim of the study is to assess the correlation of renal regional tissue saturation of oxygen (RrSO2) measured by near-infrared spectroscopy (NIRS) in preterm neonates to venous oxygen saturation (SvO2) obtained from umbilical venous catheters (UVCs), arterial oxygen saturation (SaO2) obtained from umbilical artery catheters (UACs), and capillary oxygen saturation (ScO2) from capillary heel blood draws.Study Design A secondary analysis of a prospective RrSO2 monitoring study in preterm neonates born <32 weeks gestational age. Neonates with any blood gas obtained during RrSO2 monitoring were included. RrSO2 was compared with simultaneous O2 saturation using non-parametric Mann Whitney U-test and Spearman correlation coefficient.Results In 35 neonates, 25 UVC, 151 UAC, and 68 heel capillary specimens were obtained. RrSO2 was lower than the median SvO2 (58.8 vs. 78.9, p <0.01), SaO2 (51.0 vs. 93.2, p <0.01), and ScO2 (62.2 vs. 94.25, p <0.01). RrSO2 values correlated to both SaO2 and ScO2 (r = 0.32; p <0.01, r = 0.26; p = 0.03), but not SvO2 (r = 0.07; p = 0.74).Conclusion In this secondary analysis, RrSO2 was consistently lower than blood gas O2 saturations and correlated with SaO2 and ScO2 but not SvO2. Lack of a correlation to SvO2 could be due to the small UVC sample size limiting statistical power. Future studies should prospectively evaluate if RrSO2 truly primarily reflects venous oxygenation in preterm neonates.Key Points
Keywords: near infrared spectroscopy; renal oxygenation; preterm; neonate; oxygen